The Effect of the Geometrical Relations of the Opera Spaces on the Acoustical Performance - Al-Khafaji, Saba Jabar; Mety, Peter Khammu; Al-Khoja, Sara Munther (Iraqi Journal of Architecture and Planning, 2009)